TRANSFORMATION OF MAQÂSHID Al-SYARÎ’AH (An Overview of the Development of Islamic Law in Indonesia) - Absori .; Aidul Fitriciada Azhari; M. Mu’inudinillah Basri; Fatkhul Muin (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2016)
Abstract:This study is part of an effort to systematize the basic conception of the values of the sharia as the foundation in the life of nation and state life, where the orientation is to embody the essence of the religious life through the maqâshid al-syarî`ah. Islam as al-dîn has been providing the basics of life of Muslims through the al-Qur’an and as-Sunnah. Both of these contain guidance values of human life, including in running the sharia for Muslims. Sharia (syarî`ah) in perspective of terminology is